Peran Sekolah Sebagai Agen Sosalisasi Politik dalam Mendukung Pendidikan Politik Bagi Siswa di SMK Negeri 2 Mandrehe - Gulo, Iman Krisman Jaya; Harefa, Anugerah Tatema; Bawamenewi, Adrianus; Hulu, Syukur Kasieli (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to determine the role of the school as an agent of political socialization in supporting political education for students at SMK Negeri 2 Mandrehe, to determine the school's strategy as an agent of political socialization in supporting political education for students is still not maximally carried out at SMK Negeri 2 Mandrehe. This research uses a qualitative method with a descriptive approach. The tools used by researchers in collecting data are recordings, pictures, and field notes. Recording using a recording device, namely a cellphone (recording all conversations), the results of the picture as real evidence, then a notebook that serves to record all conversations with data sources. Based on the results of the research found that the role of schools as agents of political socialization in supporting political education for students at SMK Negeri 2 Mandrehe is to provide understanding to students to participate in elections and school efforts in introducing politics to students. The school's strategy as a political socialization agent in supporting political education for students at SMK Negeri 2 Mandrehe is that it can be done through the Civics learning process which provides an understanding of participation in political activities, as well as activities carried out in schools such as the election of osis administrators and political socialization for novice elections conducted by bawaslu in schools that provide understanding to students in participating in political activities.